Initiation by White Snake and the Acquisition of Supernatural Knowledge - Kuusela, Tommy (Religionsvidenskabeligt tidsskrift, 2022)
ABSTRACT: This paper explores narratives about eating the flesh of a dragon or whiteserpent. It is argued that these narratives can be interpreted as examples of initiation. The snake’s association with wisdom is a common motif in Scandinavian folklore,stretching back at least to the Middle Ages. The author argues that folklore accounts of eating a white snake correspond symbolically to initiation. Different texts explain and legitimise how certain persons gain abilities such as wisdom, second sight, and the ability to understand the language of birds or other animals. This motif shows continuity over time and space and does not have to have taken place as an actual ritual for theinterpretation to be valid, particularly as, in the 19th century, such stories legitimised such people’s position in society as ‘cunning folk’.